Evaluation of the Phytochemical Content of Some Edible Grains Marketed in Nigeria - S. A. Odoemelam; C. I. Osu (E-Journal of Chemistry)
Five food grains (groundnut, millet, wheat, guinea corn and breadfruit) commonly consumed in Nigeria were evaluated for their phytochemical contents. The results revealed that the grains contained 0.60-1.24% alkaloid, 0.82-2.27% flavonoid, 0.03-0.05% saponin, 0.50-0.60% tannins, 2.40-2.80% phenols and 0.17-0.30% phytic acid. Dietary implications of these constituents are highlighted